Epidemiological, Radiographical, and Laboratorial Characteristics of Chinese Asymptomatic Cases With COVID-19: A Systematic Review and Meta-Analysis - Yan, Haohao; Ding, Yudan; Guo, Wenbin (Frontiers in Public Health, 2022)
The comprehensive understanding of the characteristics of asymptomatic cases are helpful for the identification and management of patients with asymptomatic COVID-19 infection. Four electronic databases were searched from December 1, 2019 to February 8, 2022 for relevant articles. Data synthesis, subgroup analysis, and sensitivity analysis were performed on the included studies. I2 and Q tests were applied to evaluate heterogeneity across studies. The risk of publication bias was assessed and visualized using a funnel plot. A total of 45 studies consisting of 2,655 patients with no symptoms at the screening point were included. Pooled results showed that in China, 65% of initial no-symptoms COVID-19 patients did not present any COVID-19-related symptom during follow-up or by end of disease course (asymptomatic infections). High proportions of initial no-symptoms COVID-19 patients (76%) and patients with asymptomatic infection (55%) had abnormal CT features at the screening point. High proportion of patients with asymptomatic infection had been detected Ig G+ (72%) and/or Ig M+ (57%) at the screening point. The chest CT scan and SARS-CoV-2-specific antibody testing could serve as effective supplementary methods to identify asymptomatic cases in the early stage of SARS-CoV-2 infection. However, the chest CT scan and the SARS-CoV-2-specific IgM and IgG testing should not replace reverse transcription–polymerase chain reaction (RT-PCR) for screening in asymptomatic patients. The combination of repeated RT-PCR, chest CT scans, and the SARS-CoV-2-specific IgM and IgG testing should be performed for those highly suspected SARS-CoV-2 infections. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/#recordDetails, identifier: CRD 42021261130.